Question
Asked Dec 9, 2019
17 views
Given h(x) = 2x
- 6x + 5, find h(- 6).
h(- 6) =
help_outline

Image Transcriptionclose

Given h(x) = 2x - 6x + 5, find h(- 6). h(- 6) =

fullscreen
check_circle

Expert Answer

Step 1

Given:

help_outline

Image Transcriptionclose

h(x)= 2x2 – 6x +5 ...(1)

fullscreen
Step 2

To find h(-6), put x= -6...

help_outline

Image Transcriptionclose

h(x) = 2x² – 6x + 5 h(-6) = 2(-6)* –6(-6) + 5 = 2x36+ 36 +5 = 72 + 41 = 113

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Solutions are written by subject experts who are available 24/7. Questions are typically answered within 1 hour.*

See Solution
*Response times may vary by subject and question.
Tagged in

Math

Algebra

Polynomials